Effectiveness of Acceptance and Commitment Couple Therapy on Marital Satisfaction, Marital Function and Obsessive Symptoms in Couples with Obsessive Compulsive Disorder - Alirezaei, Amir; Izady, Raziyeh (Shahroud Journal of Medical Sciences, 2025)
Background: Obsessive-compulsive disorder is a psychological condition that hinders one's ability to function properly because of persistent and unproductive thoughts and behaviors and has been suggested to contribute to distress in romantic relationships. The purpose of this study was to explore how couple therapy rooted in acceptance and commitment can improve marital happiness and functioning while decreasing obsession symptoms in individuals with obsessive-compulsive disorder.Material and method: The current research was a quasi-experimental study with a pre-test-post-test design. The target population consisted of all patients diagnosed with obsessive-compulsive disorder who were referred to psychological service centers in Isfahan in 2022. Twenty-six married patients with obsessive-compulsive disorder were chosen through convenience sampling and randomly divided into experimental and control groups (13 individuals in each group). The experimental group underwent an intervention based on acceptance and commitment, involving 10 therapy sessions lasting 90 minutes per week (five group sessions and five sessions with both partners present). Meanwhile, the control group remained on a waiting list and received no experimental treatment. The two groups were evaluated before and after the program using the ENRICH Marital Satisfaction (EMS), The Family Functioning Scale (FFS), and The Yale-Brown Obsessive-Compulsive Scale (Y-BOCS). In this research, statistical calculations were conducted using SPSS-21 software by performing the Analysis of Covariance (ANCOVA).Results: The analysis of covariance results indicated that during the post-test phase, the experimental group displayed significant enhancement marital satisfaction, marital function, and decreased obsessive symptom scores with a statistical significance (P<0.05). Moreover, the intervention had a 58 percent impact on post-test obsessive symptom scores. Conclusion: The results of this research suggest that utilizing acceptance and commitment couple therapy can enhance marital satisfaction, improve functioning, and decrease obsession symptoms, making it a viable treatment option for individuals with obsessive-compulsive disorder